Trickster theatre : the poetics of freedom in urban Africa - Shipley, Jesse Weaver (African expressive cultures., 2015)
Trickster Theatre traces the changing social significance of national theatre in Ghana from its rise as an idealistic state project from the time of independence to its reinvention in recent electronic, market-oriented genres. Jesse Weaver Shipley presents portraits of many key figures in Ghanaian theatre and examines how Akan trickster tales were adapted as the basis of a modern national theatre. This performance style tied Accra's evolving urban identity to rural origins and to Pan-African liberation politics. Contradictions emerge, however, when the ideal Ghanaian citizen is a mythic hustler who stands at the crossroads between personal desires and collective obligations. Shipley examines the interplay between on-stage action and off-stage events to show how trickster theatre shapes an evolving urban world.